HOW ERGONOMIC FACTORS CONTRIBUTE TO EMPLOYEES' PERFORMANCE - Masterizki, Hanantya Gilang; Armanu, Armanu; Irawanto, Dodi Wirawan (Universitas Brawijaya, Indonesia, 2019)
The objective of this article is to explain how ergonomic factors such as lighting, temperature, noise, and computer's monitor can contribute to employees' performance. This study took place in Graduate and Post-graduate Program (Pascasarjana) of Faculty of Economics and Business, University of Brawijaya. Ten informants that work as an employee in the faculty were involved in this research. Using an in-depth interview with those informants, the researcher found that ergonomic factors did contribute to the employee's performance. We found that a comfortable room with adequate lighting, pleasant temperature, minimum noise, and the appropriate monitor can ensure employees' comfortability in their workplace, which will also enhance their performance. Most of the employees admit that they already satisfied with what their work has to offer. These findings correlate with six indicators of performance, where quality and quantity were achieved, every job was completed on time, all facilities were able to be utilized, and all employees were able to perform team works to get the job done, without the need of being supervised. We, as a researcher, suggest that every organization should manage their working environment to become as ergonomic as possible, so that their employees may achieve higher performance.